Membangun Kepercayaan Pengguna Melalui Transparansi Akad Syariah Sebagai Strategi Peningkatan Penggunaan Fintech Syariah - Ansori, Moh. Asep Zakariya; Wahyudin, M. Wanri; Alawiah, Hanan; Syuardiansyah, Syahra Putri; Suhendri, Suhendri (Ikatan Da'i Indonesia, 2026)
The development of Islamic fintech in Indonesia faces user trust challenges despite offering financial services based on sharia principles. This research aims to analyze the influence of sharia contract transparency on user trust and its implications for increasing Islamic fintech usage. The research method employs a literature study with a qualitative approach, analyzing trusted journal articles using keywords